KINDS OF ORGANIC MATTER AND CALCITE CONTRIBUTION ON THE CHANGE OF IRON AND MANGANESE IN SOIL AND UPTAKE BY MAIZE AT NORTH ACEH INCEPTISOL - Khusrizal (Talenta Publisher, 2015)
The Inceptisols is a soil in great amount and widely distributed in Indonesia, even in the province of Aceh Inceptisols is the most extensive amount. The Inceptisols were found from lowland up to highland, and their properties are very varied. Commonly, the soil fertility of the Inceptisols of lowland is low. Calcite and Organic Matter are the easy matter found, and to be considered as a better soil amendment. While maize is improved varieties of crops that its production constantly to be increased. This experiment was conducted in order to study the contribution of organic matter as well as calcite contribution to the change of iron and manganese in soil and uptake by maize at North Aceh Inceptisol. Kinds of organic matter that was used consist of cow manure and water hyacinth (60:40). The fully randomized design has been conducted that consists of two combined treatment factors with three replicated. The factor is related to the kinds of organic matter was 0.0, 2.0, 3.0 and 4.0 ton ha-1 and calcite was 0.0, 1.0 and 1.5 ton ha-1. The results showed that the application of organic matter and calcite significantly affect levels of iron and manganese in the soil and plants. Dose organic material 4 ton ha-1 and calcite 1.5 tons ha-1 are able to increase at the highest level of the iron content of the soil, while the dose of organic materials 4 ton ha-1 and calcite dose 0.0-1.0 tonnes ha-1 is the best for the increasing of manganese in the soil. The highest content of iron and manganese of maize crop was obtained at a dose of 6.0 tons ha-1 of organic matter without calcite application.